2011
DOI: 10.1038/gene.2011.33
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for malaria selection of a CR1 haplotype in Sardinia

Abstract: Complement receptor 1 (CR1) levels have been associated with malarial susceptibility and/or severity of the disease in different population groups, and CR1 is a receptor for Plasmodium falciparum. In this study, multiple CR1 single-nucleotide polymorphisms (SNPs) showed strong evidence of population differentiation between Sardinian and other European ethnic groups. Cross population algorithms comparing haplotype structure and differences in haplotype and allele frequency distribution provided additional suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 31 publications
4
21
2
Order By: Relevance
“…The AkeA researchers found that the gene pool in the Sardinians of the particularly remote mountainous region is relatively small (Carru et al 2003;Pes et al 2004). For example, the local people have small red blood cells, which is thought to protect them against malaria and help prevent blood clots (Kosoy et al 2011). Our results from Scenario C showed that infant mortality in Sardinia is lower in the mountainous areas where a large part of our centenarians mainly come from.…”
Section: Discussionsupporting
confidence: 60%
“…The AkeA researchers found that the gene pool in the Sardinians of the particularly remote mountainous region is relatively small (Carru et al 2003;Pes et al 2004). For example, the local people have small red blood cells, which is thought to protect them against malaria and help prevent blood clots (Kosoy et al 2011). Our results from Scenario C showed that infant mortality in Sardinia is lower in the mountainous areas where a large part of our centenarians mainly come from.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, African population, Another SNP of CR1, A4828G (R1601G), is highly prevalent in malaria endemic areas of Africa, but a study in Gambia showed that it was not associated with severe malaria [19]. However, the findings of a similar study of various European populations supported the role CR1 (CD35) polymorphism in malarial infection [20]. The work of A. Srivastava & B. Mittal for Indian population suggests that decreased expression of complement receptor 1 (CR1) on erythrocytes confirm reduced clearance of immune complexes, conferring inter individual variation for gallbladder cancer (GBC) susceptibility.…”
Section: Discussioncontrasting
confidence: 30%
“…We also identified several regulatory variants for the CR1 gene whose product is involved in complement activation and immune complex formation during malaria infection 41,42 . CR1 has two eQTLs (chr1:g.207275799G>A and chr1:g.207667190G>C) and 9 sQTLs.…”
Section: Resultsmentioning
confidence: 99%